Effects of traditional Chinese medicine formula Le-Cao-Shi on hepatitis B: In vivo and in vitro studies. (15th November 2019) - Zhao, Qing; Ren, Xia; Chen, Min; Yue, Shi-Jun; Zhang, Meng-Qi; Chen, Kai-Xian; Guo, Yue-Wei; Shao, Chang-Lun; Wang, Chang-Yun
Abstract: Ethnopharmacological relevance: Formula Le-Cao-Shi (LCS) is a traditional Chinese medicine (TCM), which has long been used as a folk remedy against hepatitis B in China. The present study was conducted to evaluate the anti-hepatitis B effects of aqueous extract of LCS in vivo and in vitro . Materials and method: we investigated the anti-HBV effects of LCS in vivo and in vitro with duck hepatitis B model and HepG2.2.15 cell line model, respectively. The serologic and cellular biomarkers and the histopathological changes were examined. Results: By a duck hepatitis B model, the extract of LCS was found to restrain the expressions of duck hepatitis B surface antigen (DHBsAg), hepatitis B e antigen (DHBeAg), and HBV-DNA (DHBV-DNA). Moreover, LCS could decrease the levels of aspartate and alanine aminotransferases (AST and ALT) and ameliorate duck liver histological lesions. Correspondingly, in a HepG2.2.15 cellular model, LCS could also significantly inhibit the secretions of HBsAg and HBeAg. Conclusion: LCS exerted potent anti-hepatitis effects against the infection of HBV. The above results demonstrated the first-hand experimental evidences for the anti-hepatitis B efficiency of LCS. Our study provides a basis for further exploration and development of this promising compound prescription to treat hepatitis B disease. Graphical abstract: Image 1